The application of instrumentation system on a contactless robotic triage assistant to detect early transmission on a COVID-19 suspect - Niko Azhari Hidayat; Prisma Megantoro; Abdufattah Yurianta; Amila Sofiah; Shofa Aulia Aldhama; Yutika Amelia Effendi (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
This article discusses the instrumentation system of airlangga robotic triage assistant version 1 (ARTA-1), a robot used as a contact-free triage assistant for Coronavirus disease (COVID-19) suspects. The triage process consists of automatic vital signs check-up as well as the suspect’s anamnesis that in turns will determine whether the suspect will get a specific care or not. Measurements of a suspect’s vital conditions, i.e. temperature, height, and weight, are carried out with sensors integrated with the Arduino boards, while a touch-free, hand gesture questions and answers is carried out to complete anamnesis process. A portable document format (PDF) format of the triage report, which recommends what to do to the suspect, will then be automatically generated and emailed to a designated medical staff.